Exposure to bisphenol A and gender differences: from rodents to humans evidences and hypothesis about the health effects - Lidia Caporossi; Bruno Papaleo (MDPI AG, 2015)
Bisphenol A (BPA) interacts with the endocrine system and seems to produce different effects in relation to gender. The objective of the study was to clarify the possible health effects of exposure to BPA in relation to gender. A literature search was performed using three different search engines: Medline, PubMed and Scopus. Data on both animals and humans showed that BPA acts as a xenoestrogen and interacts with the androgens' metabolism, producing different outcomes: uterotropic effects, decreasing sperm production, stimulation of prolactin release. Gender difference plays a key role in understanding the real toxic effects, the BPA serum concentrations were, all the time, higher in male subjects, possibly due to the difference in androgen-related enzyme activity levels, compared with the healthly female subjects, to equal levels of exposure; while higher BPA levels in women have been associated with a variety of conditions including obesity, endometrial hyperplasia, recurrent miscarriages, and polycystic ovarian syndrome. The data collected are sufficiently robust to raise concerns about the potentially deleterious impact of BPA on humans, even with some methodological limitations; the different impact of BPA in men and in women is documented and of a certain interest. In toxicology it is necessary to assess effects in relation to gender differences, in order to set up prevention plans in the work environment targeting the specific risk.